Supporting Students With Disabilities With Positive Behavioral Interventions and Supports in the Classroom: Lessons Learned From Research and Practice. (December 2021) - Meyer, Katherine; Sears, Sandra; Putnam, Robert; Phelan, Crystal; Burnett, Alicia; Warden, Susannah; Simonsen, Brandi
Positive behavioral interventions and supports (PBIS) is a widely adopted framework to support the social, emotional, and behavioral growth of all students. This article addresses two key questions related to supporting students with disabilities through PBIS: (a) Why focus on universal classroom PBIS practices?—without support, students with disabilities experience poor outcomes—and (b) How do you implement PBIS in classrooms that support all students?—differentiate and intensify supports.